1978
DOI: 10.1103/physrevd.18.4767
|View full text |Cite
|
Sign up to set email alerts
|

Two-well oscillator

Abstract: Very accurate eigenvalues of the two-well oscillator (H(k, k) = pkx + Ax ) are obtained by a nonperturbative method. The splitting between the pairs of lower eigenvalues is found to be remarkably well estimated by the WKB approximation. It is observed that the scaling properties of the exact eigenvalues with 'respect to the parameters in the Hamiltonian are retained in the WXB approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 13 publications
9
41
0
3
Order By: Relevance
“…This value strictly depends on the number of the basis functions and will increase for a larger set of them. Since the potential shifted by 1/(4λ) is positive definite, some authors have reported the highly accurate positive definite eigenvalues E n + 1/(4λ) [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value strictly depends on the number of the basis functions and will increase for a larger set of them. Since the potential shifted by 1/(4λ) is positive definite, some authors have reported the highly accurate positive definite eigenvalues E n + 1/(4λ) [14].…”
Section: Resultsmentioning
confidence: 99%
“…We can also use the scaling properties of the double-well potential to find the properties of a general Hamiltonian H(k, λ) = −p 2 − kx 2 + λx 4 from a more simpler one which we have studied here H(1, β) = −p 2 − x 2 + βx 4 . Using the transformation of variable from x to k 1/4 x, we find the following scaling properties [14,26] …”
Section: Resultsmentioning
confidence: 99%
“…The most common nonperturbative methods such as the variational method [6], semi-classical approximation method, e.g. the WKBJ method [9], the Hill determinant method [11] etc, suffer from the limitation that these are seldom systematically improvable and are often tailored for the specific problem under investigation.. Hence the need arises to develop a nonperturbative method that is, in principle, applicable to general quantum systems, as well as, systematically improvable.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, several schemes have been forwarded which go beyond the ordinary perturbation theory. These include: variational [6] methods, variation-perturbation method [7], Gaussian approximation scheme [8], the WKBJ method [9], the Hartree approximation scheme [10], the Hill-determinant method [11] and its variants [12], the method of modified perturbation theory [13], the Boguliobov-transform methods [14] and many more [15]. The most common nonperturbative methods such as the variational method [6], semi-classical approximation method, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…in accordance with (8). It is interesting to notice that the first N + 1 equations in (25) may be written as an inhomogeneous linear system …”
Section: Matrix Representation Of the Schrödinger Operator In Hpmmentioning
confidence: 94%